Understanding fracture mechanism and behaviour of ultra-high strength concrete using mesoscale modelling. (July 2020) - Thilakarathna, P.S.M.; Kristombu Baduge, K.S.; Mendis, P.; Chandrathilaka, E.R.K; Vimonsatit, V.; Lee, H.
Highlights: Development and analysis of 3D numerical mesoscale model is presented. Realistic aggregate geometric shapes and placing algorithms are discussed. Cohesive contact can be used successfully to model Interfacial Transition Zone. Transgranular fracture in UHSC can be observed under static uniaxial compression. Damage can initiate in any of the three phases and subsequently progress. Abstract: Ultra High Strength Concrete (UHSC) is a composite material of which the fracture and damage behavior is highly dependent on its constituent phases. Damage and fracture behavior of UHSC is markedly different from the Normal Strength Concrete (NSC) due to its brittle behavior and crushing through the aggregate. This complex behaviour and influence of properties of constituent phases to the mechanical properties of UHSC cannot be understood using conventional testing on materials. To better understand this complex fracture behavior and influence of the phases, a different approach is required. Mesoscale modelling where concrete is modelled as a three-phase material which consists of aggregates, mortar and Interfacial Transition Zone (ITZ), can be considered as a potential method to address these issues. In this paper, development of mesoscale models of concrete using various shapes of aggregates and methods of intersection checks and placing algorithms are presented. Accurate material model selection for the constituent phases and efficient meshing methods are also discussed. Fracture and damage behavior of UHSC under uniaxial compression is investigated using the developed mesoscale models. Transgranular fracture of UHSC under uniaxial compression was modelled successfully and found that the damage initiation can occur in any of the three phases in mesoscale. Effect of various parameters on the damage behavior of UHSC is discussed and the feasibility of using this powerful tool of mesoscale modelling is discussed with the challenges.